The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11920-014-0442-3
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Bricks and Mortar: Recent Research on Substance Use Disorder Recovery Management

Abstract: Scientific advances in the past 15 years have clearly highlighted the need for recovery management approaches to help individuals sustain recovery from chronic substance use disorders. This article reviews some of the recent findings related to recovery management: a) continuing care, b) recovery management checkups, c) 12-step or mutual aid, and d) Technology-based interventions. The core assumption underlying these approaches is that earlier detection and re-intervention will improve long-term outcomes by mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 46 publications
1
44
0
Order By: Relevance
“…Although recovery remains a contested term, there is a general agreement that this is a complex phenomenon that is individual and that occurs over time (Betty Ford Consensus Group [1]). Indeed, Dennis, Scott and Laudet [2] have argued that it takes around ve years before recovery can be considered to be 'self-sustaining'. There is now a growing consensus that recovery is a multi-factorial and non-linear process, with the Betty Ford group de ning addiction recovery as "voluntarily maintained lifestyle characterised by sobriety, personal health and citizenship" [1, p. 222].…”
Section: Introductionmentioning
confidence: 99%
“…Although recovery remains a contested term, there is a general agreement that this is a complex phenomenon that is individual and that occurs over time (Betty Ford Consensus Group [1]). Indeed, Dennis, Scott and Laudet [2] have argued that it takes around ve years before recovery can be considered to be 'self-sustaining'. There is now a growing consensus that recovery is a multi-factorial and non-linear process, with the Betty Ford group de ning addiction recovery as "voluntarily maintained lifestyle characterised by sobriety, personal health and citizenship" [1, p. 222].…”
Section: Introductionmentioning
confidence: 99%
“…The current clinical perspective on treating substance use disorders embraces a chronic disease model in recognition of the fact that for many individuals, multiple treatment episodes are required to achieve long-term recovery (Hser et al, 1997; McKay, 2001; McKay and Hiller-Sturmhöfel, 2011; Dennis and Scott, 2007). As with any chronic disease, the objectives for promoting successful long-term management of substance use disorders feature regular screening, monitoring, and assistance linking with additional care as needed (McKay, 2009; Dennis et al, 2014). Extending treatment and recovery services beyond an initial treatment episode is intuitively appealing from a clinical perspective but also implies long-term costs, creating a need to find both effective and economically viable continuing care strategies for individuals with substance use disorders.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent meta-analysis of 19 studies concluded that, on average, continuing care was more effective than minimal or no continuing care as an extension to formal modalities of treatment (Blodgett et al, 2014). Continuing care approaches that are more adaptive, have longer durations, and use motivational incentives to increase participation in treatment performed better than average (Dennis et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…However, the danger has been that these goals are not equally accessible to all of those in treatment -particularly those with complex and severe problems associated not only with their substance use but also with mental health, family relationships, trauma and so on -and it has led to concerns that individuals not ready for recovery are being hastened to the exit door not because they are ready for stable recovery (Dennis, Scott, & Laudet, 2014 estimated that "self-sustaining recovery" takes around five years) but because specialist services do not get paid otherwise! That the recovery agenda gained prominence in the UK around the time of the Global Financial Crisis has meant that the agenda for change and growth associated with the recovery movement has been linked to reducing treatment costs and expenditure with the workforce fearing that the push for self-reliance and mutual aid is simply an attack on professional services, and an attempt to reduce the cost burden associated with specialist addiction support.…”
Section: The Curse Of Definitionsmentioning
confidence: 99%